QEEG index for early detection of imbalanced conditions during aerobatics - Tharawadeepimuk, Kittichai; Wongsawat, Yodchanan (2013 Asia-Pacific Signal and Information Processing Association Annual Summit and Conference, 2013)
In this paper, the brain activity was studied and observed while person was in the loss of balance state due to vestibular system disorder. Brain activity was recorded as QEEG data which was analyzed by the Z-scored FFT method. The experimental results showed brain activities in the positions O 1 , O 2 , P 3 , P 4 , P Z , T 5 , and T 6 in the forms of topographic map (Absolute Power) and brain connectivity (Amplitude Asymmetry). It was represented in the topographic map that, during the loss of balance state, brain areas at occipital and parietal lobes have high intensity level of brain processing. For brain connectivity, the results clearly showed the brain connections while subjects were trying to maintain their balances. These strong connections were represented by red lines between O 1 , O 2 positions (occipital lobe) and P z (parietal lobe), F z (frontal lobe) and C z (central lobe). Similarly, there were strong connections between T 5 and F z positions and T 5 and T 6 positions. On the other hand, the connection between T 6 and F z was found to be a weak connection. The analysis of results can be employed in the alarm system of pilot during aerobatics.